2021
DOI: 10.15304/rge.30.2.7190
|View full text |Cite
|
Sign up to set email alerts
|

Firm Growth: A review of the empirical literature

Abstract: The objective of this research is to review and unify the empirical literature that identifies the determining factors for firm growth. A list of 165 articles forms the backbone of the present review of the empirical literature on firm growth. Based on this review, we provide a synthesis of numerous determinant factors associated with firm growth. Specifically, we enumerate and detail the determining factors in three blocks: entrepreneur’s idiosyncratic features, firm’s internal factors, and factors external t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 135 publications
(234 reference statements)
0
15
0
Order By: Relevance
“…In this paper, we use different variables from previous studies, namely the number of study groups and the number of courses as variables to measure the growth in the complexity of the business process model. The complexity of business processes is one indicator of organizational growth, as stated by Vaz in 2021, where organizational structure is one factor that determines the growth of an organization [8]. This study is the first to propose using the number of study groups and the number of courses as variables in measuring the growth in complexity of business process models.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this paper, we use different variables from previous studies, namely the number of study groups and the number of courses as variables to measure the growth in the complexity of the business process model. The complexity of business processes is one indicator of organizational growth, as stated by Vaz in 2021, where organizational structure is one factor that determines the growth of an organization [8]. This study is the first to propose using the number of study groups and the number of courses as variables in measuring the growth in complexity of business process models.…”
Section: Introductionmentioning
confidence: 93%
“…8, which shows that the growth of the business process model in 8 courses has the smoothest curve and is the closest to linear; this is represented by the value of the variable b, which is greater than the other curves. While the most vertical curve is the growth curve of the 10 courses business process model, but this Based on the business process model complexity growth curve presented in Fig.8, Fig.9, and Fig.10, it is found that the growth curve for the complexity of the business process model as a function of the number of study groups has no predictable pattern.…”
mentioning
confidence: 90%
“…According to Backman and Charlie (2020), the age of operational managers is vital for young and small firms of which sole proprietorship firms with older operational managers have better survival results. Vaz (2021) found that as managers' age progresses, firms end up posting lesser sales growth and lower investment. To the contrary, the probability of the firm's survival goes up.…”
Section: Table 1: Descriptive Statisticsmentioning
confidence: 99%
“…Frešer, Širec and Tominc (2020) define corporate growth as a very complex phenomenon, which may be rooted in the demographic characteristics of the companies, sufficient financial resources, the intensity of entrepreneurial orientation or their intangible capital that leads to greater heterogeneity and diversity in the definition of high-growth companies. Vaz (2021) states that according to empirical studies the key internal factors that may bring an advantage to the firm's growth are vision and mission, the objective(s) of the firm, strategic planning, size, localization, human resources, financial resources, and organizational structure.…”
Section: Literature Reviewmentioning
confidence: 99%